The 2011 Joint Sino–U.K. Protein Symposium. (21st September 2011) - Chang, Zengyi; Isaacs, Neil
Abstract : As part of the celebrations marking its Centenary, the Biochemical Society held a joint meeting in Shanghai with the Chinese Protein Society to commemorate the many long-standing collaborations between biochemists from the U.K. and China. Under the overall theme of structural biology of proteins, presentations covering both historical and current research were given by a number of leading biochemists from both countries. Papers based on these talks have been prepared for this issue of Biochemical Society Transactions .